The development of a solar driven water purifier for emergency use - Dackhammar, Pontus; Hansson, Edvin (My University, 2020)
Natural disasters are a growing global problem, which often negatively affect the availability of clean water and sanitation by polluting water sources and damaging water infrastructure. From the year 1995 to 2005, 90% of all disasters were caused as a consequence of weather-related events. Out of these disasters, flooding and storms accounted for approximately three quarters all of events. The aim of this thesis work was therefore to develop a solar driven water purifier, to be used in an emergency setting by providing 100 persons with clean water every day. The work involved a pre-study, generation and screening of multiple concepts, detailed design and calculations as well as a commercial analysis. The final product is a stackable, robust, and compact system, designed to reduce the costs related to transportation. The purification process consists of a pre-filtration system and an ultraviolet disinfection unit, that reduces microbiological contaminants by a factor of 104. The system receives power via solar cells and has a battery that can provide the system with power up to 3 days without any solar radiation. There is a flexible clean water tank with a capacity of 250 liters attached to the body of the system. The analytical result, in particular for the UV-unit, needs physical testing to be validated. Therefore is it essential to build a prototype, preferably using the drawings provided in the report, to verify the product’s performance. There is also a need for more detailed design regarding the electrical system before a potential commercial launch. The estimated production cost for the system is 3369 SEK and given a unit margin of 50%, this translates to a competitive theoretical listing price compared to similar products on the market. By comparing the estimated total cost, including expected maintenance, the results indicates that I would take approximately 7 months of usage for the final product to have a significantly lower total cost than the LifeSaver Jerry Can, identified as one of the main competitors.
Keywords: water, purification, ultraviolet, emergency, natural disaster